Eco-Innovation Inputs in the EU-Member States in the Years, 2010-2018 - Pakulska, Jolanta (Studia Ecologiae et Bioethicae, 2020)
Eco-innovations are an important factor in economic growth in the modern economy. For this reason, the EU places great emphasis on analysing the level of eco-innovation of the economies of member countries. The instrument used for this purpose is the Eco-Innovation Scoreboard, which shows how much the level of eco-innovation in the Member States differs from the EU average, while indicating the strengths and weaknesses of each country. In the face of growing environmental problems, the role of projects minimising the negative impact of economic activity on the environment, is constantly growing. Eco-innovations play an important role in this process. The aim of the article is to analyse the diversity of expenditure on eco-innovation in EU countries, as well as to the factors making up the overall expenditure indicator. Eco-innovation inputs are designed to support eco-innovation and cover both financial and human aspects. Eco-innovation activities in various types of organisations are considered here, including those in research enterprises and institutions. In the analysis of eco-innovation inputs, the government`s environmental and energy R&D appropriations and outlays, total R&D personnel and researchers, and total value of green early stage investments, are all taken into account. The study uses a descriptive method, such as analysing the dynamics of changes in time, as well as statistical methods enabling researchers to assess the diversity of indices between individual Member States.